PRAGMATIC ASPECTS OF SPEECH ACTS: A CROSS-LINGUISTIC PERSPECTIVE - Tanduk, Rita (University of Kuningan, 2023)
Effective intercultural communication is a cornerstone of today's globalized world, necessitating an exploration of the pragmatic aspects of speech acts from a cross-linguistic perspective. This research delves into the complex interplay between language, culture, and politeness strategies within the contexts of Bahasa Indonesia and Malay. Using a comprehensive datasets collected through observational field study in diverse naturalistic settings, including workplaces, educational institutions, and everyday social contexts, research examines the performance and interpretation of requests, apologies, compliments, and refusals. The findings reveal a shared preference for indirect and polite language when making requests in both linguistic communities, underlining the universality of politeness strategies. While Bahasa Indonesia speakers tend to employ explicit expressions of regret in apologies, Malay speakers adopt a more subtle approach. Compliments showcase differences, with Bahasa Indonesia speakers favoring direct expressions of admiration and Malay speakers employing nuanced language. Refusals demonstrate stark contrasts, with Malay speakers utilizing indirect strategies and Bahasa Indonesia speakers opting for directness. This study contributes to the growing discourse on cross-linguistic and cross-cultural pragmatics, emphasizing the importance of considering both linguistic diversity and cultural norms in understanding intercultural communication. This research, grounded in real-world interactions, calls for continued exploration of trans-cultural threads in speech act usage and offers valuable insights for enhancing intercultural competence. While acknowledging the study's limitations, researcher invites future research endeavors to delve deeper into the intricate world of speech acts and intercultural communication.